2016
DOI: 10.1590/1809-2950/14743623012016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on the frequency of lymphedema and other complications after surgery for breast cancer

Abstract: Objective: this study assessed the influence of pre-operative body mass index (BMI) has upon lymphedema, scar tissue adhesion, pain, and heaviness in the upper limb at two years after surgery for breast cancer. Methods: retrospective analysis of 631 medical records of women who underwent surgery for breast cancer and were referred to the Physiotherapy Program at Prof. Dr. José Aristodemo Pinotti Women's Hospital of the Center for Integral Women's Health Care, CAISM/UNICAMP between January 2006 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Similarly, in another study conducted with patients undergoing general surgery, it was found that high BMI was not associated with a higher pain score (2). A positive relationship between BMI and postoperative pain was not seen in another study of breast cancer patients (31). Similarly, in a study conducted on patients who underwent tubular gastrectomy, no relationship was found between BMI and postoperative pain (7).…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, in another study conducted with patients undergoing general surgery, it was found that high BMI was not associated with a higher pain score (2). A positive relationship between BMI and postoperative pain was not seen in another study of breast cancer patients (31). Similarly, in a study conducted on patients who underwent tubular gastrectomy, no relationship was found between BMI and postoperative pain (7).…”
Section: Resultsmentioning
confidence: 92%
“…Keterbatasan LGS bahu pasca MRM disebabkan oleh beberapa faktor, namun faktor yang diduga berperan penting timbulnya keterbatasan LGS yaitu imobilisasi lama dan proses penyembuhan luka operasi. 4,14,15,16 Pada penelitian ini terjadi imobilisasi pada ekstremitas atas di sisi operasi pada kelompok kontrol. Hal ini dapat menyebabkan terjadinya perlekatan intra dan ekstraselular pada kapsul dan ligamen, yang berakhir dengan timbulnya reaksi fibrosis.…”
Section: Diskusiunclassified